Os impactos de técnicas não farmacológicas na impulsividade - Yuri de Castro Machado (2023)
Impulsivity is a multifaceted phenomenon characterized by different cognitive and behavioral patterns that can lead to immediate and medium-to-long-term dysfunctional consequences. The treatment of impulsivity has been a major challenge in the field of mental health, as there are not many well-described and scientifically validated tools that are effective in improving the overall well-being of these individuals. Among the general approaches that can be used for this purpose, pharmacological interventions, physical activities, and psychotherapeutic approaches such as cognitive-behavioral therapy (CBT), social and emotional skills training, and impulse control therapy stand out. In this study, we will analyze three other promising non-pharmacological techniques for impulse control, namely Yoga, Mindfulness, and non-invasive neuromodulation. To do so, we conducted three systematic reviews in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) criteria. The review protocols were registered in the International Prospective Register of Systematic Reviews (PROSPERO). The Medical Subject Headings (MeSH) were used to select the descriptors for the search. The article search was conducted in the PubMed, Scopus, Science Direct, and Embase databases. Only articles in English were included, and there was no restriction on the publication period of the included articles. The articles included in this systematic review were independently selected by two different reviewers. They performed the selection in two stages, the first based on the reading of titles and abstracts, and the second with the full-text reading. In case of divergence in the article selection, a third reviewer was consulted. The quality of the studies included in these systematic reviews was assessed using the Cochrane Risk of Bias tool. At the end of the article selection process, 6 articles were analyzed in the Yoga study, 18 in the Mindfulness study, and 18 in the non-invasive neuromodulation study (9 articles on Transcranial Direct Current Stimulation (tDCS) and 9 on Transcranial Magnetic Stimulation (TMS)), and a meta-analysis of their data was performed. Based on the results obtained, Yoga and Mindfulness techniques emerge as promising in the treatment of impulsivity, demonstrating effectiveness in various psychometric tests and scales. These therapeutic approaches are easy to implement, scalable, and cost-effective, making them viable for both clinical and public health contexts. On the other hand, studies on tDCS and TMS still lack sufficient evidence to support their implementation in the treatment of impulsivity. The lack of standardization in the stimuli used and the diversity in study designs hinder the definition of effective protocols. Therefore, future research will be necessary to establish more specific parameters and clear intervention standards for these non-invasive neuromodulation techniques in the context of impulsivity